The CMS event builder demonstrator and results with Myrinet - Antchev, G.; Cano, E.; Cittolin, S.; Erhan, S.; Faure, B.; Gigi, D.; Gutleber, J.; Jacobs, C.; Meijers, F.; Meschi, E.; Ninane, A.; Orsini, L.; et al. (Computer physics communications, 2001)
The data acquisition system for the CMS experiment at the Large Hadron Collider (LHC) will require a large and high performance event building network. Several switch technologies are currently being evaluated in order to compare different architectures for the event builder. One candidate is Myrinet. This paper describes the demonstrator which has been setup to study a small-scale (16×16) event builder based on PCs running Linux connected to Myrinet and Ethernet switches. A detailed study of the Myrinet switch performance has been performed for various traffic conditions, including the behaviour of composite switches. Results from event building studies are presented, including measurements on throughput, overhead and scaling. Traffic shaping techniques have been implemented and the effect on the event building performance has been investigated. The paper reports on performances and maximum event rate obtainable using custom software, not described, for the Myrinet control program and the low-level communication layer, implemented in a driver for Linux. A high performance sender is emulated by creating a dummy buffer that remains resident in the network interface and moving from the host only the first 64 bytes used by the event building protocol. An approximate scaling in N is presented assuming a balanced system where each source sends on average data to all destinations with the same rate.